Students as Agents of Islamic Technopreneurship in the Digital Era: Evidence from Islamic Higher Education in Indonesia - Syukron, Ahmad; Astuti, Fauziah; Suradi, Didi; Dahri, Harapandi (Institut Agama Islam Negeri (IAIN) Curup, 2025)
The rapid development of digital technology has created new opportunities and challenges in higher education, particularly for Muslim students who are expected to integrate Islamic values with entrepreneurial practices. This study analyzes students as agents of Islamic technopreneurship in the digital era by examining the influence of digital literacy on Islamic entrepreneurship. The research employed a quantitative descriptive design with linear regression analysis, involving 48 first-year students from the Early Childhood Islamic Education (PIAUD) and Islamic Education Management (MPI) programs at STIT Nusantara Bekasi who participated in the 2025 orientation program themed “Independent and Visionary Students: Building Islamic Entrepreneurship Based on Halal, Sunnah, and Local Wisdom in the Digital Era. Data were collected through Likert-scale questionnaires and analyzed using descriptive statistics, normality tests, homogeneity tests, and linear regression. The results show that the classical assumptions of normality and homogeneity were met, supporting the validity of the regression model. Furthermore, the findings reveal that digital literacy significantly influences Islamic entrepreneurship, with a contribution of 20.1%. This indicates that students’ digital competencies positively strengthen entrepreneurial values such as honesty, trustworthiness, and social benefit. The study concludes that students play an essential role as agents of Islamic technopreneurship, capable of integrating digital innovation with halal business principles and local wisdom. Practically, the results emphasize the importance for higher education institutions to enhance curriculum and training programs that merge digital skills with Islamic ethical values, thereby preparing competitive and visionary Muslim technopreneurs for the global marketplace.